KEBUTUHAN AIR IRIGASI TANAMAN MENTIMUN (Cucumis sativus L) PADA MEDIA TANAM CAMPURAN TANAH DAN ARANG DALAM POLIBAG - Pangaila, Shilviana Sischa; Kalesaran, Leo H.; Rantung, Ruland A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
The purpose of this study is to calculate the number of water needs of the cucumber using a mixture of soil and wood charcoal in the polyester and to examine how a mixture of wood - based media has affected the growth of the cucumber. The study was designed to use a complete random with three experiments of land proportions and charcoal, and one control treatment without charcoal, treatment A (soil : charcoal 4:1), treatment of B (soil : charcoal 3:2), treatment of C (soil : charcoal 2 : 2), the treatment of K (control soil without charcoal) with 4 replications for each treatment, making the number of experiments 16. Research shows that the variant analysis of the amount of irrigation water used during the growth of cucumber plants from treating soil and charcoal to an average of A (4:1) = 10,035.33 ml r; B (3:2) = 10,698.33 ml; C (2 :2) = 11,060 ml; And K (without charcoal) = 8,716.67 ml, it turns out there is a significant difference between treatment. As for the growth of the plant and the growth of the fruit yield no significant difference. The use of wood charcoal as a medium to grow has a bearing on the formation of a cucumber.